Climate change vulnerability in Southern African Cities : building knowledge for adaptation - Tiepolo, Maurizio; Macchi, Silvia (Springer Climate,, 2014)
In recent decades, extreme rains and drought have struck urban regions in Africa like never before. Nevertheless, limited information is available on which to base development of early warning systems, identification of high-risk zones, and formulation of local action plans. This book is about how to build the knowledge necessary for planning adaptation to climate change in Sub-Saharan cities. It brings together lessons learned from international development actions conducted by a number of scholars in disciplines ranging from meteorology and hydrogeology to urban planning and environmental management. Selected methods to assess the impacts of extreme weather and ecological stress are presented along with possible approaches to improve the adaptive capacity of Sub-Saharan cities through institutional measures at the local government level. The book is addressed to graduate students, researchers, and practitioners interested in enhancing their knowledge and skills in order to integrate climate change into applied research and development projects in urban Africa.